Organizational Citizenship Behavior (OCB) as an Intervening Variable of Motivation, Competence and Total Quality Management (TQM) on Employee Performance of ABC Hospital in Jombang - Istanti, Enny (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Everyone's top priority should be their health. The aim of this research is to characterize the following: motivation, competence, total quality management, and organizational citizenship behavior (OCB); the impact of each on performance; the relationship between motivation and TQM; the relationship between TQM and OCB; and the relationship between OCB and performance. Partial Least Square (PLS) Analysis is a quantitative method used to analyze the connection between variables in order to investigate objective theory. The conversation's outcomes Performance is significantly impacted by motivation, competence, TQM, and OCB. The findings indicate that OCB is significantly impacted by motivation, competence is significantly impacted by motivation, TQM is significantly impacted by TQM, and OCB is significantly impacted by employee performance. Additionally, motivation has a significant impact on employee performance.